Konsep Manajemen Sumber Daya Dalam Paradigma Pendidikan Islam - Aulia Pusfita Sari; Musyarapah Musyarapah; Nasiruddin Sidqi (Journal on Education, 2024)
This research investigates Islamic education resource management methods and their impact on the effectiveness of Islamic education institutions. Through a qualitative approach and literature study, this research analyses concepts, history and approaches in Islamic education resource management. The research method involved collecting data from various sources, including books, journals and official documents relevant to this topic. Data analysis was conducted by summarising the findings and identifying relevant patterns and trends. The results show that Islamic education resource management includes managing human, material, financial and spiritual resources by applying Islamic values in every aspect. The history of the development of Islamic education management shows an evolution from the golden age to the modern era, characterised by challenges and adaptation to changing times. There are various approaches to Islamic education management, such as operational, behavioural, system and quantitative approaches, which provide a comprehensive framework for managing Islamic education institutions effectively and efficiently. By understanding the concepts, history and approaches in Islamic education resource management, it is hoped that Islamic education institutions can achieve their educational goals more effectively, as well as make a positive contribution to the development of Muslim society as a whole. This research provides valuable insights for Islamic education practitioners in designing management strategies that are in line with Islamic values and the demands of the times.